EFFECTIVENESS PROBLEM BASED LEARNING ON STUDENTS CRITICAL THINKING SKILLS TO SUPPORT ESD - Fitria, Anita; Anggreini, Anggreini; Rosidin, Undang; Viyanti, Viyanti; Suana, Wayan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research purposed to determine the effectiveness of problem based learning on students critical thinking skills especially on physics material about alternative energy and its role in supporting ESD. The design used in this research is quasi-experimental design with a non-equivalent control group design. The sample are class X E as the experimental class and then class X D as the control class at SMAN 14 Bandar Lampung. The test instrument have a value from Cronbach'Alpha is 0.862. The result of average N-Gain was 0.63 with a moderate category while the average n-gain of critical thinking skills in the control class was 0.41 with a moderate category. This shows that the indicators of critical thinking skills increased significantly, the sig. Value was 0.000 <0.05 so it can be concluded that there is asignificant difference between the average n-gain of critical thinking skills of students experimental class and the control class. This novelty from this research are contribution by integrating Problem-Based Learning (PBL) integrated Education for Sustainable Development (ESD) By using real-world sustainability issues as learning contexts, the study aims to enhance students' critical thinking skills in meaningful and relevant ways. The findings have practical implications for educators in designing instructional strategies to increase critical thinking and sustainability awareness. Theoretically, this research supports the role of PBL as an effective pedagogical approach for 21st-century education with the goals of sustainable development.